Arsitektur Regionallisme dalam Perancangan Jogja Planning Galery - Mu’adz Muhammad Naufal; Desrina Ratriningsih (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
The Jogja Planning Gallery (JPG) is a strategic initiative designed by the Yogyakarta City Government to address the challenges of increasingly rapid and uncontrolled urban development. Yogyakarta is known as a historic city with high appeal in the tourism and education sectors, and as a favorite place to live, especially for the elderly. The high interest of people from outside the region to settle in Yogyakarta has led to a surge in development that is not in line with the established urban spatial plan. For this reason, the Yogyakarta City Government plans to build the Jogja Planning Gallery (JPG) which will be located at Jalan Malioboro No. 56 and No. 54, precisely on the land of Teras 2 Malioboro and the DIY DPRD Building. This location was chosen because it is part of the philosophical axis – an imaginary axis created by Sultan Hamengkubuwono I as the basis for the spatial planning of Yogyakarta City. JPG is designed as an information gallery that presents the development vision of the Yogyakarta City Government, as well as a form of transparency regarding future city development plans. This gallery will also display the evolution of the face of Yogyakarta City from the past, present, and future. Through JPG, it is hoped that the public will gain a better understanding of the direction of urban development and be encouraged to actively participate in creating a comfortable, sustainable, and distinctive city.   Keywords:, ,